A review on the security issues of telemedicine network - Rabiul, Ahasan; Chowdhury Akram, Hossain; Md. Saniat Rahman, Zishan (2014)
Telemedicine is currently a promising area of research as day by day the need of better medical support is increasing. There had been numerous researches done in this particular field with many aspects. In our paper we mainly focused on the review of the system and few common security threats which have a huge influence on the quality of the service. In our paper we also reviewed literatures which suggested few possible solutions to the threats.